Goodpasture's Syndrome and Silica: A Case Report and Literature Review - James Dahlgren; Marla Wardenburg; Trevor Peckham (Case Reports in Medicine)
We report a case of Goodpasture's syndrome following chronic low level and an acute, high level of exposure to crystalline silica. A 38-year-old male tilesetter was admitted to the emergency room with dyspnea and respiratory failure. He reported that his symptoms had developed over the previous week after inhaling a large amount of dust while dry-sanding and sweeping a silica-based product used to fill cracks in a cement floor. Over the following days, his pulmonary function declined and he developed acute renal failure. Tests of antiglomerular basement membrane antibody were positive and renal biopsy revealed global glomerulonephritis. He was diagnosed with Goodpasture's syndrome and treated with steroids, plasmapheresis, and hemodialysis. This man had a history of childhood asthma and a remote, one pack-year history of cigarette use. He used the flooring product for seven years prior to the inciting event, however, previous jobs had utilized significantly smaller amounts. Goodpasture's syndrome and other autoimmune diseases have been reported in association with silica exposure. The acute onset following high level silica exposure in this previously healthy man, suggest that clinicians should investigate silica exposure as a causal factor in cases of Goodpasture's syndrome.